2017
DOI: 10.1371/journal.pone.0165363
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid antagonist SLV326 induces convulsive seizures and changes in the interictal EEG in rats

Abstract: Cannabinoid CB1 antagonists have been investigated for possible treatment of e.g. obesity-related disorders. However, clinical application was halted due to their symptoms of anxiety and depression. In addition to these adverse effects, we have shown earlier that chronic treatment with the CB1 antagonist rimonabant may induce EEG-confirmed convulsive seizures. In a regulatory repeat-dose toxicity study violent episodes of “muscle spasms” were observed in Wistar rats, daily dosed with the CB1 receptor antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Examples of peripheral CB 2 R agonists are listed in Table 8 below. Regarding the use of CB 1 R antagonists [136], of note is that side effects of CB 1 R antagonism may include neuropsychiatric sequalae (e.g., anhedonia and anxiety), pain, hyperalgesia, hypertension, and pro-convulsive effects [136,371]. Examples of CB 1 R antagonists are listed in Table 9 below.…”
Section: Gat228 (R-enantiomer)mentioning
confidence: 99%
“…Examples of peripheral CB 2 R agonists are listed in Table 8 below. Regarding the use of CB 1 R antagonists [136], of note is that side effects of CB 1 R antagonism may include neuropsychiatric sequalae (e.g., anhedonia and anxiety), pain, hyperalgesia, hypertension, and pro-convulsive effects [136,371]. Examples of CB 1 R antagonists are listed in Table 9 below.…”
Section: Gat228 (R-enantiomer)mentioning
confidence: 99%
“…The seizures analyzed in the present study occur during chronic treatment with the CB1 antagonist SLV326, as it was reported previously in [26]. Since the method to elicit the seizures was reported extensively there, here it will be repeated only in short.…”
Section: Subjects and Local Field Potential Recordingmentioning
confidence: 85%
“…Conversely, CB 1 antagonists, such as rimonabant, induce spontaneous convulsive seizures [25][26][27] or increase the occurrence of existing seizures in several in vitro [28] and in vivo [29][30][31] epilepsy or seizure models. There is also evidence in humans: partial seizures were observed in a patient treated with rimonabant for obesity, who had a history of idiopathic generalized epilepsy [32].…”
Section: Introductionmentioning
confidence: 99%